Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing

Spatio-temporal resolution of taxonomic and functional microbiome of Lonar soda lake of India reveals metabolic potential for bioremediation - Chakraborty, Jaya; Rajput, Vinay; Sapkale, Vibhavari; Kamble, Sanjay; Dharne, Mahesh (Chemosphere, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Lonar Lake, India; a hypersaline and hyperalkaline extremophilic ecosystem having a unique microbial population has been rarely explored for bioremediation aspects. MinION-based shotgun sequencing was used to comprehensively compare the microbial diversity and functional potential of xenobiotic degradation pathways with seasonal changes. Proteobacteria and Firmicutes were prevalent bacterial phyla in the pre-monsoon and post-monsoon samples. Functional analysis from SEED-subsystem and KEGG database revealed 28 subsystems and 18 metabolic pathways for the metabolism of aromatic compounds and xenobiotic biodegradation respectively. Occurrence of N-phenyl alkanoic, benzoate, biphenyl, chloroaromatic, naphthalene, and phenol degradation genes depicted varied abundance in the pre-monsoon and post-monsoon samples. Further, KEGG analysis indicated nitrotoluene degradation pathway (ko00633) abundant in post-monsoon samples, and the benzoate degradation pathway (ko00362) predominant in 19LN4S (pre-monsoon) than 18LN7S (post-monsoon) samples. The abundant genes for benzoate degradation were pcaI: 3-oxoadipate CoA-transferase, alpha subunit, pcaH: protocatechuate 3,4-dioxygenase, beta subunit, and pcaB: 3-carboxy-cis, cis-muconate cycloisomerase, and 4-oxalocrotonate tautomerase. This metagenomic study provides a unique blueprint of hitherto unexplored xenobiotic biodegradation genes/pathways in terms of seasonal variations in the Lonar Lake, and warrants active exploitation of microbes for bioremediation purposes.